PENERAPAN MODEL PEMBELAJARAN KOOPERATIF MAKE A MATCH DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Iis Irmawati; Yani Setiani; Indiana Marethi (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
Mathematical communication is the delivery of ideas or ideas that involve physical and mental activities that must be possessed bystudents in solving a problem in mathematics. For this reason, an appropriate learning model is needed, one of which is the Make AMatch cooperative learning model. The main objective of this research is to find out whether there are differences in achievement andimprovement in mathematical communication skills of students who use the Make A Match cooperative learning model with studentswho do not use the Make A Match cooperative learning model. This research was conducted using a quasi-experimental method. Thedesign used was non-equivalent control group design while the population in this study were all grade VII students of SMP Negeri 4Serang in the 2016/2017 school year. Sampling uses a purposive sampling technique and the instruments used are tests. The resultsshowed that: (1) The final achievement of mathematical communication skills of students who get the Make A Match cooperativelearning model with a scientific approach is better than students who get learning with a scientific approach. (2) Improvement of thefinal achievement of mathematical communication skills of students who get the Make A Match cooperative learning model with ascientific approach is better than students who get learning with a scientific approach.